T-bet overexpression enhances CAR T cell effector functions and antigen sensitivity - M. Eric Kohler; Kole R DeGolier; Terry J Fry; Amalia M Rivera-Reyes; Jennifer M Cimons; Samuel D Burciaga; Michael C Yarnell; Amanda J Novak (Journal for ImmunoTherapy of Cancer)
Background T cells modified to express a chimeric antigen receptor (CAR) are successful against B-lineage malignancies but fail to induce durable remissions in up to half of patients and have shown limited efficacy against other types of cancer. Strategies to improve CAR T cell potency and responses to low antigen densities without inducing CAR T cell dysfunction or limiting persistence are necessary to expand durability of remissions.Methods We overexpressed T-bet in human and mouse CAR T cells to mimic exposure to signal 3 cytokines during T cell priming to promote T helper cell 1 (Th1) polarization of CD4+CAR T cells with the goal of enhancing antitumor activity. Using human CAR T cells and xenograft models we interrogated the impact of T-bet overexpression on CAR T cell antitumor activity in vitro and in vivo. We also used a syngeneic murine CAR T cell model to study the impact of T-bet overexpression on long-term persistence and secondary responses to tumor rechallenge.Results T-bet overexpression reduced expression of the Th2 cytokine interleukin 4 and promoted polyfunctional production of Th1-associated cytokines in response to CAR stimulation. T-bet overexpression enhanced some effector functions in vitro but did not improve CAR T cell-mediated control of leukemia expressing high levels of antigen in vivo. T-bet overexpression also improved effector function of murine CD19 CAR T cells with no impairment to the persistence or ability of persistent CAR T cells to re-expand and clear a secondary leukemia challenge. Finally, T-bet overexpression promoted enhanced in vitro function against leukemia expressing low levels of CD19, which translated to improved control of CD19lo leukemia in vivo by human C19 CAR T cells containing a 4-1BB costimulatory domain.Conclusions Together, our data demonstrate that T-bet overexpression induces a reduction in Th2 cytokine production, an increase in polyfunctional Th1 cytokine production and enhances 4-1BB CAR T cell activity against cancers expressing low levels of target antigen without promoting a loss in functional CAR T cell persistence.